2021
DOI: 10.1007/s11069-021-05064-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual hurricane evacuation intentions during the COVID-19 pandemic: insights for risk communication and emergency management policies

Abstract: The U.S. 2020 hurricane season was extraordinary because of a record number of named storms coinciding with the COVID-19 pandemic. This study draws lessons on how individual hurricane preparedness is influenced by the additional risk stemming from a pandemic, which turns out to be a combination of perceptions of flood and pandemic risks that have opposite effects on preparedness behavior. We conducted a survey in early June 2020 of 600 respondents in flood-prone areas in Florida to obtain insights into househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In addition to its specific findings concerning COVID-19 and flooding, this study provides insights that may contribute to broader comparative research on COVID-19 and concurrent hazards (Botzen et al forthcoming;Ishiwatari et al 2020;McBride et al 2020;Simonovic et al 2021). By examining how risk response varies across hazards on the basis of stakes, immediacy, dread, and polarization, we contribute to efforts to understand risks not only in terms of probability and severity but also in terms of their qualitatively differing physical and social content.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition to its specific findings concerning COVID-19 and flooding, this study provides insights that may contribute to broader comparative research on COVID-19 and concurrent hazards (Botzen et al forthcoming;Ishiwatari et al 2020;McBride et al 2020;Simonovic et al 2021). By examining how risk response varies across hazards on the basis of stakes, immediacy, dread, and polarization, we contribute to efforts to understand risks not only in terms of probability and severity but also in terms of their qualitatively differing physical and social content.…”
Section: Discussionmentioning
confidence: 82%
“…Examining these differences can help us understand responses to each hazard on its own as well as yield theoretical insights into more general issues surrounding risk perception and response. It can also contribute to disaster management in multihazard scenarios, a major concern that has intensified during the pandemic (Botzen et al forthcoming;CONVERGE 2020;Ishiwatari et al 2020;Simonovic, Kundzewicz, and Wright 2021).…”
Section: Original Articlementioning
confidence: 99%
“…Specifically, individuals perceived the threat of COVID-19 were more likely to hesitated whether to evacuate to the designated evacuation center with various preventive measures or whether to participate in volunteer activities ( 65 ). Another study conducted in the US during the hurricane season revealed that COVID-19 risk perception negatively affected response strategies against hurricanes ( 22 ). Overall, our findings enrich the research regarding the compound flooding risk in the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the multi-hazard context, different hazards could stimulate different levels of risk perception ( 21 ), which can have an intertwined effect on different disaster-response strategies. As pointed out by Botzen, the perception of the COVID-19 pandemic had an opposite effect on evacuation intention during the subsequent hurricane season ( 22 ). To better recognize how the public responds to COVID-19 when overlapped with the flood, the current study examined the relationship between flood risk perception and preventive behaviors for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Both He et al ( 2021 ) and Qiu et al ( 2021 ) discuss how the pandemic impacted the mental well‐being of hospital staff. The studies within this theme cover many more varieties such as the pandemic impact on businesses (Lee et al, 2022 ), on specific slum areas in Indian cities (Das et al, 2021 ), and on how household preparedness for hurricanes (Botzen et al, 2022 ).…”
Section: Thematic Overview Of Covid‐19 Pandemic Studies: Basic Motor ...mentioning
confidence: 99%